Strategic alignment and performance measurement: the case of TM Berhad / Prof Dr Normah Hj Omar and Hazeline Ayoup - Omar, Normah; Ayoup, Hazeline (Research Management Institute (RMI), 2013)
Managing companies' performance is a dynamic activity which is subjects to continuous changes from time to time. It encompasses various internal and external organizational factors exhibit conflict of interest between companies' strategic mission, vision and strategies and the individuals who work in the organizations. Rapid changes in the business environment globally especially with the fast moving technological advancement has forced companies to manage their performance to sustain its competitive advantages and improve performance. Numerous performance management tools have been developed to facilitate performance management processes along the way. Among numerous performance management tools developed, the BSC has received great attention from researchers and practitioners from worldwide since it was introduced in the early 1990s. A lot of studies have been conducted to explore and understand its benefit, shortcoming, implementation and implication (Srite, Galvin, Anuja and Karahanna, 2007; Anand, Sahay and Saha, 2005; Davis and Albright, 2004; Braam and Nijssen, 2004; and Maiga and Jacobs, 2003). However, it is aware that implementing BSC is not an easy task. Kaplan and Norton (2001) mentioned that many BSC implementation fail. Atkinson (2006) supported this claim founded that the successful story of BSC implementation is just about 30 percent (Atkinson, 2006).